Decline in hunter offtake of blue duikers in Bioko Island, Equatorial Guinea - Grande Vega, M.; Farfán, M.A.; Ondo, A.; Fa, J.E. (Wiley, 2016)
The blue duiker (Philantomba monticola) is an abundant and widely distributed ungulate in continental sub‐Saharan Africa. High hunting pressure throughout its range may be particularly threatening to the persistence of island populations of the species. In this study, we assessed offtake of blue duikers in Pico Basilé, Bioko Island, Equatorial Guinea. We recorded the number of animals shot or snared by 46 commercial hunters over a 33‐month period, and the location (elevation) of each animal hunted. From this, we estimated catch per hunter (CH), catch per hunting day (CD) and catch per unit effort (CPUE). The number of duikers shot or snared across the study period, significantly declined within the mid‐altitude range (901–1500 m). There were no significant drops in CH or CPUE at low or high altitudes for snared animals. The ratio of immature‐to‐adult animals hunted increased significantly over time within the mid‐altitude range. We suggest that these trends in offtake, especially in the more heavily hunted mid‐altitudes of the study area, indicate a decline in the population within this range. If this situation is widespread throughout the island, it is likely that unregulated bushmeat hunting will have devastating consequences to the biodiversity of Bioko Island, particularly for heavily hunted species that are naturally less abundant.